2021
DOI: 10.1111/codi.15654
|View full text |Cite
|
Sign up to set email alerts
|

Risk and consequences of dehydration following colorectal cancer resection with diverting ileostomy. A systematic review and meta‐analysis

Abstract: Aim: This systematic review aims to assess dehydration prevalence and dehydrationrelated morbidity from diverting ileostomy compared to resections without ileostomy formation in adults undergoing colorectal resection for cancer.Method: MEDLINE, Embase, CENTRAL and ClinicalTrials.gov were searched for studies of any design that reported dehydration, renal function and dehydration-related morbidity in adult colorectal cancer patients with diverting ileostomy (last search 12 August 2020). Bias was assessed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 57 publications
(146 reference statements)
1
14
0
Order By: Relevance
“…In our study patients with prior radiotherapy did not develop AKI, while among subjects with prior radiochemotherapy 11% developed AKI. In a recent review, Borucki et al [26] reported that significant dehydration was common following ileostomy and was linked with AKI and had a long-term impact on renal function.…”
Section: Aki -Acute Kidney Injury Ckd-epi -Chronic Kidney Disease Epidemiology Collaboration Egfr -Estimated Glomerular Filtration Rate Imentioning
confidence: 99%
“…In our study patients with prior radiotherapy did not develop AKI, while among subjects with prior radiochemotherapy 11% developed AKI. In a recent review, Borucki et al [26] reported that significant dehydration was common following ileostomy and was linked with AKI and had a long-term impact on renal function.…”
Section: Aki -Acute Kidney Injury Ckd-epi -Chronic Kidney Disease Epidemiology Collaboration Egfr -Estimated Glomerular Filtration Rate Imentioning
confidence: 99%
“…Moreover, PI creation is itself responsible for morbidity, including intestinal atrophy, leakage from the stoma appliance, skin irritation, bowel obstruction, enterocutaneous fistula, high-output stoma, renal impairment, parastomal hernia or prolapse and hospital readmission, so in the case of patients without AL its utility should be balanced with its complications [36,[39][40][41][42].…”
Section: Discussion and Con Clus Ionsmentioning
confidence: 99%
“…Lastly, independently from the indication to create a PI, it is important to underline that in the literature the real utility and advantages of a stoma are still under debate [28][29][30][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51].…”
Section: Discussion and Con Clus Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the Cr at discharge has normalized in rate of readmission for dehydration or renal failure was 17%, and that 55% of these patients (18/33) had a concomitant AKI using the Acute Kidney Injury Network criteria [7]. A recent meta-analysis has linked ileostomies to long-term renal dysfunction and cites a casecontrol analysis of 101 patients, 18% of whom were on surgical services, to support the claim that dehydration causes these renal issues [16]. The claim that dehydration alone causes long-term renal dysfunction is challenged by the finding of Fish et al demonstrating that outpatient intravenous fluid administration did not prevent readmissions [2].…”
Section: Discussionmentioning
confidence: 99%